Role of Bcl2-associated Athanogene 3 in Turnover of Gap Junction Protein, Connexin 43, in Neonatal Cardiomyocytes - Ghasemi Tahrir, Farzaneh (Sci Rep, 2019)
Any pathological stress that impairs expression, turnover and phosphorylation of connexin 43 (Cx43), one of the major proteins of gap junctions, can adversely impact myocardial cell behavior, thus leading to the development of cardiac arrhythmias and heart failure. Our results in primary neonatal rat ventricular cardiomyocytes (NRVCs) show that impairment of the autophagy-lysosome pathway dysregulates degradation of Cx43, either by inhibiting lysosomal activity or suppressing the level of Bcl2-associated athanogene 3 (BAG3), a stress-induced pleiotropic protein that is involved in protein quality control (PQC) via the autophagy pathway. Inhibition of lysosomal activity leads to the accumulation of Cx43 aggregates and suppression of BAG3 significantly diminished turnover of Cx43. In addition, knock-down of BAG3 reduced the levels of Cx43 by dysregulating Cx43 protein stability. Under stress conditions, expression of BAG3 affected the state of Cx43 phosphorylation and its degradation. Furthermore, we found that BAG3 co-localized with the cytoskeleton protein, α-Tubulin, and depolymerization of α-Tubulin led to the intracellular accumulation of Cx43. These observations ascribe a novel function for BAG3 that involves control of Cx43 turnover under normal and stress conditions and potentially for optimizing communication of cardiac muscle cells through gap junctions.